The Importance of Appropriate Dosing of Nonvitamin K Antagonist Oral Anticoagulants for Stroke Prevention in Patients with Atrial Fibrillation - Beyer-Westendorf, Jan; Fay, Matthew; Amara, Walid (TH Open, 2021)
Preventing thromboembolic events, while minimizing bleeding risks, remains challenging when managing patients with atrial fibrillation (AF). Several factors contribute to current dosing patterns of nonvitamin K antagonist oral anticoagulants (NOACs), including patient characteristics, comorbidities, and physician judgment. Application of NOAC doses inconsistent with the drug labels may cause patients to receive either subtherapeutic (increasing stroke risk) or supratherapeutic (increasing bleeding risk) anticoagulant levels. In clinical practice, under- or over-dosing of NOACs in patients with AF is not uncommon. This analysis of prospective and retrospective registry and database studies on NOAC use in patients with AF (with at least 250 patients in each treatment arm) showed that under-dosing may be associated with reduced effectiveness for stroke prevention, with similar or even increased bleeding than with the standard dose. This may reflect underlying conditions and patient factors that increase bleeding despite NOAC dose reduction. Such factors could drive the observed overuse of reduced NOAC dosages, often making the prescription of reduced-dose NOAC an intentional label deviation. In contrast, over-dosing more likely occurs accidentally; instead of providing benefits, it may be associated with worse safety outcomes than the standard dose, including increased bleeding risk and higher all-cause mortality rates. This review summarizes the main findings on NOAC doses usually prescribed to patients with AF in clinical practice.
Keywords: anticoagulants; atrial fibrillation; stroke